2014
DOI: 10.4240/wjgs.v6.i7.136
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelial cysts and cystic lymphangiomas: Under-recognized benign cystic lesions of the pancreas

Abstract: Contrast enhanced computed tomography demonstrated that the cysts had thin walls, without calcifications, pancreatic duct dilation or pancreatic parenchyma invasion. Endoscopic ultrasound with fine needle aspiration (EUS/FNA) confirmed the diagnosis of a lymphoepithelial cyst in 3 patients, one of whom was spared an operation and continues to do well after 6 years. Eleven patients had a resection: 3 pancreaticoduodenectomies, 7 distal pancreatectomies, and 1 enucleation. The median size of the cysts was 3 cm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…8 Twenty-three new studies since that period were additionally included. 3,6, After adding the 29 patients presented in this study, a cohort of 214 LECs was available for review (Table 3). Subsequent analysis of these patients showed that LECs were most commonly seen in men (79%) with a median age of 57 years at diagnosis.…”
Section: Pathologic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Twenty-three new studies since that period were additionally included. 3,6, After adding the 29 patients presented in this study, a cohort of 214 LECs was available for review (Table 3). Subsequent analysis of these patients showed that LECs were most commonly seen in men (79%) with a median age of 57 years at diagnosis.…”
Section: Pathologic Assessmentmentioning
confidence: 99%
“…3,4 However, the increasing use of abdominal cross-sectional imaging has resulted in an increase in the detection of asymptomatic benign pancreatic cysts. 5,6 LECs are often misdiagnosed as a pancreatic cystic neoplasm, resulting in surgical resection. Since LECs are entirely benign lesions, correct preoperative diagnosis is important in order to avoid unnecessary surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not clearly specified for each patient. $The study by Konstantinidis et al [28] stated that the median age was 37.5 (range 19-69) and the median size was 9.2 cm (range 2.3-16.5). Two patients presented with abdominal pain and 2 patients were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Los linfangiomas quísticos son tumores benignos y poco frecuentes que resultan de la obstrucción de la circulación linfática por una malformación congénita del sistema linfático, una enfermedad inflamatoria o una neoplasia (Chairi et al, 2021). Por su parte, el LQP es una entidad más rara, tanto así, que se estima representan menos del 0,2% de todas las lesiones quísticas del páncreas (Konstantinidis et al, 2014). Es una de aquellas neoplasias quísticas raras, respecto de las cuales la información disponible es muy limitada (Santes & Chan, 2016).…”
Section: Discussionunclassified